1988
DOI: 10.1152/ajpregu.1988.254.4.r567
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive atrial natriuretic factor is increased in ovine model of endotoxemia

Abstract: A bolus of Escherichia coli endotoxin (1.5 micrograms/kg) was administered to chronically instrumented sheep. Immunoreactive atrial natriuretic factor (IR-ANF) was measured in extracted plasma by radioimmunoassay. There was a thirteenfold increase in IR-ANF 2 h after endotoxin administration, and IR-ANF levels remained significantly elevated during the first 6 h. A marked diuresis and natriuresis occurred between 4 and 6 h. ANF not only affects renal function but is also associated with decreased cardiac outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Therefore, it appears that peptidases that degrade ANF are not induced during systemic inflammation, but rather it is the secretion of ANF that is induced. These data are consistent with the observed elevations in plasma ANF after LPS challenge that have been observed in sheep (48) and dogs (49). Given the inverse correlation between plasma OpdB activity and plasma ANF levels, we believed it plausible that OpdB released by trypanosomes into the rat circulation could modulate plasma ANF levels.…”
supporting
confidence: 92%
“…Therefore, it appears that peptidases that degrade ANF are not induced during systemic inflammation, but rather it is the secretion of ANF that is induced. These data are consistent with the observed elevations in plasma ANF after LPS challenge that have been observed in sheep (48) and dogs (49). Given the inverse correlation between plasma OpdB activity and plasma ANF levels, we believed it plausible that OpdB released by trypanosomes into the rat circulation could modulate plasma ANF levels.…”
supporting
confidence: 92%
“…The first observations that ANP may play a role during endotoxic shock came from animal studies in which ANP was elevated within 2–6 hours after lipopolysaccharide injection [32,33]. Subsequent studies in critically ill humans showed an association of ANP with various cardiac physiological parameters [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Based on physiological principles, the plasma levels of ANP would be expected to be lower in states of hypovolaemia (Levin et al 1998). However, ANP is increased during experimental endotoxic shock in sheep (Lubbesmeyer et al 1988;Redl et al 1992;Hinder et al 1996), and this is also seen in septic human subjects (Mitaka et al 1990). In endotoxic rats, plasma ANP concentrations have been shown initially to decrease, but then increase by 6 h and remain increased at 24 h (Aiura et al 1995).…”
Section: Introductionmentioning
confidence: 99%